Joint Inversion of Coseismic and Early Postseismic Slip to Optimize the Information Content in Geodetic Data: Application to the 2009 Mw6.3 L'Aquila Earthquake, Central Italy. Issue 10 (30th October 2019) - Ragon, Théa; Sladen, Anthony; Bletery, Quentin; Vergnolle, Mathilde; Cavalié, Olivier; Avallone, Antonio; Balestra, Julien; Delouis, Bertrand
Abstract: When analyzing the rupture of a large earthquake, geodetic data are often critical. These data are generally characterized by either a good temporal or a good spatial resolution, but rarely both. As a consequence, many studies analyze the coseismic rupture with data that also include one or more days of early postseismic deformation. Here, we invert simultaneously for the coseismic and postseismic slip with the condition that the sum of the two models remains compatible with data covering the two slip episodes. We validate the benefits of this approach with a toy model and an application to the 2009 M w 6.3 L'Aquila earthquake, using a Bayesian approach and accounting for epistemic uncertainties. For the L'Aquila earthquake, we find that if early postseismic deformation is not an explicitly acknowledged coseismic signal, coseismic slip models may overestimate the peak amplitude while long‐term postseismic models may largely underestimate the total postseismic slip amplitude. This example illustrates how the proposed approach could improve our comprehension of the seismic cycle, fault frictional properties, and the spatial and temporal relationship between seismic rupture, afterslip, and aftershocks. Key Points: Simultaneous inversion of geodetic data with different spatiotemporal resolution maximizes the information content If the early afterslip signal is neglected, coseismic slip is overestimated by 30% and postseismic slip is underestimated by a factor of 3 Early afterslip (6 days after mainshock) is mainly located at the transition zone between coseismic rupture and longer‐term afterslip